2022
DOI: 10.1007/s00062-022-01205-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Blood Patching in Spontaneous Intracranial Hypotension—Do we Really Seal the Leak?

Abstract: Purpose Epidural blood patch (EBP) is a minimally invasive treatment for spontaneous intracranial hypotension (SIH). Follow-up after EBP primarily relies on clinical presentation and data demonstrating successful sealing of the underlying spinal cerebrospinal fluid (CSF) leak are lacking. Our aim was to evaluate the rate of successfully sealed spinal CSF leaks in SIH patients after non-targeted EBP. Methods Patients with SIH and a confirmed spinal CSF leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Several studies reported low success rates due to failures in identifying the exact location of the CSF leak and blind injection of EBP. 5,12 CT myelograms and Tc99 DTPA scans are required to determine the precise location and number of CSF leaks. 4,10 Spinal leaks that occur ventrally cannot be effectively managed by EBP injection via an interlaminar approach because they cause compression dorsally, resulting in low success rates.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported low success rates due to failures in identifying the exact location of the CSF leak and blind injection of EBP. 5,12 CT myelograms and Tc99 DTPA scans are required to determine the precise location and number of CSF leaks. 4,10 Spinal leaks that occur ventrally cannot be effectively managed by EBP injection via an interlaminar approach because they cause compression dorsally, resulting in low success rates.…”
Section: Discussionmentioning
confidence: 99%
“…Several treatment strategies are available to manage SIH. These include conservative measures, targeted epidural blood patches, and lastly surgical treatment [4,6,8]. Due to the lack of randomized controlled trials, the choice of treatment depends solely on the preference and expertise of the physician [4].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the required mechanism of epidural patching, 10-20 ml of blood tend to be used. It acts in the spinal epidural space, restricting the CSF flow, and dural tamponade to seal the CSF leak sites [4,9] This procedure can be repeated more than once with intervals of 5 days and a large amount of blood should be during the repeated setting [4,8]. In the presented case, cervical-targeted EBP was performed after a failed trial of conservative options (The intraoperative details of the performed EBP were mentioned in the case presentation section).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its efficacy, actually varies from 55 to 75%, depending on the specific cause of the dural pathology and the conditions of its application performed [ 6 , 7 ]. Moreover, even if clinical improvement occurs in the early follow-up period, persisting CSF loss may perpetuate the disease and potentially result in severe long-term morbidity [ 8 , 9 ]. Notably, the persistent form of PDPH (pPDPH), while clinically observed [ 7 , 9 ], is not formally recognized in the International Classification of Headache Disorders 3rd Edition (ICHD-3).…”
Section: Introductionmentioning
confidence: 99%